PROTEASOMAL AND CALPAIN PROTEOLYSIS SYSTEMS IN DIFFERENT MOLECULAR SUBTYPES OF BREAST CANCER - E. E. Shashova; A. V. Doroshenko; L. N. Bondar; E. M. Slonimskaya; I. V. Kondakova (Сибирский онкологический журнал, 2017)
The characteristics of calpain and proteasome systems in different molecular subtypes of breast cancer were studied. Tumor samples were obtained from 147 breast cancer patients, who were not previously treated with neoadjuvant therapy. Changes in the chymotrypsin-like proteasome activity and the correlation between proteasome and calpain activities were shown in different molecular subtypes of breast cancer. No changes in the calpain activity and proteasome subunits specific for various molecular subtypes of breast cancer were found. Our results show that the proteasome function undergoes changes depending on the receptor expression by tumor cells and this aspect should be further investigated.